2016
DOI: 10.1111/afe.12156
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring carabid indicators could reveal environmental impacts of genetically modified maize

Abstract: 1 Post market monitoring of GM crops is mandatory in EU states where they are grown commercially. Carabid beetles are very sensitive to environmental changes and may be used as indicators to monitor impacts of transgenic crops. This study aimed to assess which, where and when carabids should be sampled for improved postmarket monitoring. 2 Carabids were pitfall-trapped in maize fields, field margins, alfalfa and semi-natural vegetation across three regions of NE Spain, during 2 years, and three sampling dates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 65 publications
0
14
1
1
Order By: Relevance
“…In the case of maize as a crop Lee and Albajes [31] found they could set baselines for some elements of biodiversity quality (species richness and Shannon diversity) but using only a four month period of sampling and only a few pitfall traps there were bound to be variations in the data which we have avoided here by using more traps over a longer time. Some other Miscanthus studies have contradicted this case in that they found increased biodiversity in polluted sites (Chauvat et al [32]; Hedde et al [33] or reflecting landscape richness [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of maize as a crop Lee and Albajes [31] found they could set baselines for some elements of biodiversity quality (species richness and Shannon diversity) but using only a four month period of sampling and only a few pitfall traps there were bound to be variations in the data which we have avoided here by using more traps over a longer time. Some other Miscanthus studies have contradicted this case in that they found increased biodiversity in polluted sites (Chauvat et al [32]; Hedde et al [33] or reflecting landscape richness [34].…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that a combination of sampling methods can often provide more information and greater insight than does a single method. Pitfall traps have also been used to monitor carabid abundances in conventional vs. reduced-risk insecticide management practices in Michigan, USA highbush blueberry plantations [96], to assess potential effects of transgenic corn on carabid abundance in Iowa, USA [97], and to evaluate the potential of carabids to serve as indicators of adverse environmental effects of genetically modified crops in Europe [98].…”
Section: Natural Enemies/pest Managementmentioning
confidence: 99%
“…These invertebrates can be found in almost all environments and at various soil depths. They perform important functions in this system; some of them act in the decomposition of excreta and waste of animal and vegetal origin (Yamada et al, 2007) and soil aeration and organic matter transport (Almeida and Louzada, 2009) and others in the biological control of insect pests and weeds (Lee and Albajes, 2016). Some even contribute to increase plant growth, due to their activity of incorporating manure into the soil (Scarabaeinae) (Nichols et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic changes influence both coleopterans and the rest of the biota, directly or indirectly and at various levels and intensities, e.g., by the use of agrochemicals, intensive soil rotation, and especially changes in plant composition (Baretta et al, 2014;Lee and Albajes, 2016). As groups of soil Coleoptera affect the ecosystem functionality in many ways, these insects can respond immediately to ongoing changes in the habitat and thus indicate environmental conditions on and in the soil, as well as soil balance or disturbance levels, mainly related to management practices in agriculture and forest areas (Portilho et al, 2011;Gibb et al, 2017).…”
Section: Introductionmentioning
confidence: 99%